Associations between Pathological Gambling and Psychiatric Comorbidity among Help-Seeking Populations in Hong Kong - Daniel T. L. Shek; Elda M. L. Chan; Ryan H. Y. Wong (The Scientific World Journal)
Problem gambling is complex and often comorbid with other mental health problems. Unfortunately, gambling studies on comorbid psychiatric disorders among Chinese communities are extremely limited. The objectives of this study were to (a) determine the prevalence of comorbid psychiatric disorders among treatment-seeking pathological gamblers; (b) compare the demographic profiles and clinical features of pathological gamblers with and without comorbid psychiatric disorders; (c) explore the associations between pathological gambling and psychiatric disorders and their temporal relationship. Participants (N=201) who sought gambling counseling were examined by making Axis-I diagnoses including mood disorders, schizophrenia spectrum disorders, substance use disorders, anxiety disorders, and adjustment disorder. Results showed that 63.7% of participants had lifetime comorbid psychiatric disorder. The most common comorbid psychiatric mental disorders were mood disorders, adjustment disorder, and substance use disorders. Pathological gamblers with psychiatric comorbidities were significantly more severe in psychopathology, psychosocial functioning impairment, and gambling problems than those without the disorders.